Bladder exstrophy closure in the newborn period with external pelvic fixation performed without osteotomy: A preliminary report. Issue 1 (February 2018) - Alam, A.; Blachman-Braun, R.; Delto, J.C.; Moscardi, P.R.M.; Castellan, M.; Tidwell, M.A.; Labbie, A.; Gosalbez, R.
Summary: Background: Successful primary bladder closure is the most crucial element for urinary continence in patients with classic bladder exstrophy (CBE). In the newborn period, bladder closure can be performed in the first 48 h without pelvic osteotomy or external fixation, but requires postoperative lower extremity immobilization (i.e., spica cast, Bryant's or Buck's traction). Objective: To present a novel surgical approach for primary bladder closure for CBE using two-pin external fixation without pelvic osteotomy, and without postoperative lower extremity immobilization. Study design: A retrospective chart review of patients with CBE was performed at the current institution from 2000 to 2016, including all primary bladder closures with external fixation and without osteotomy or lower extremity immobilization. Patients were discharged with the external fixator in place, which was later removed in clinic. Baseline clinical and demographic variables, and follow-up data were recorded. Results: Thirteen patients were analyzed; eight (61.5%) were male. Pre-operative intersymphysial distance was 3.68 ± 1.0 cm (2.0–5.0). Mean follow-up was 56.8 ± 40.3 months (10–131). One patient had a partial bladder neck dehiscence, due to pin displacement on postoperative day 1: he had the lowest gestational age of 34 weeks (Summary table ). Discussion: This approach used external fixation to bring the pubic bones together intra-operatively, and to decrease the tension in closing the pelvic ring and abdominal wall without osteotomy. External fixation with osteotomy and long-term immobilization, or using a spica cast without osteotomy offered the added advantage of improved wound care, due to lack of lower limb immobilization, less patient discomfort, and facilitation of mother/caregiver and newborn bonding. Conclusion: The two-pin external fixator without osteotomy as an adjunct to primary bladder closure in CBE patients was technically feasible. At the current institution this approach had an equivalent success rate to previous reports in the literature for primary bladder closure, decreased the length of hospital stay, and precluded the need for lower extremity immobilization. Early data for bladder capacity were encouraging. Summary table Baseline characteristics and follow-up outcomes of the participants. Clinical variables Mean ± SD (minimum–maximum) Gestational age (months) 38.6 ± 1.9 (34–41.2) Age at surgery (days) 2.6 ± 1.5 (1–5) Hospitalization length (days) 30 ± 15.5 (13–65) Expected bladder capacity for age (%) 55.5 ± 32.4 (11.51–108.47) Successful primary closure (%) 12 (92.3) SD, standard deviation.